Toward Arabic Scientific Digital Content - Abadou, Fadila (LANGUAGE ART, 2021)
The Arabic language is accused of failing to keep up the scientific and digital development, and being unable to assimilate science and digital knowledge production and promotion. And since the Internet has become one of the reliable sources of information, the poor Arab scientific digital content has become questioning the reliability of the information available in the Arabic language, which necessitates developing authentic Arabic content that reflects Arab identity, heritage and civilization,. Therefore, this research aims to know the challenges that the Arabic language is facing today, and the reasons that prevent it from being matched to the digital age, in addition to revealing the secret behind the low quality of Arab digital content. We conclude with some recommendations that support Arab digital content on the network.